The Relationship Of The Role Of Drug Control By Families And Health Workers With Preventive Behavior And Tbc Client Compliance During The Covid-19 Pandemic At Puskesmas Juanda Samarinda - Sholichin Sholichin; Muhammad Aminuddin; Mayusef Sukmana; Dwi Nopriyanto; Iwan Samsugito (Jurnal Kesehatan Pasak Bumi Kalimantan, 2021)
Tuberculosis is a disease that many Indonesians suffered, even arguably more terrible than the coronavirus that is now spreading in Indonesia. Therefore tuberculosis caused by the bacterium Mycobacterium tuberculosis should continue to be echoed. Tuberculosis sufferers of the victims continue to fall from year to year and always increase, as if this disease can not be treated, can not be cured, and can not be detected. The purpose of this study is to test the relationship between drug control by families and health workers with the preventive and compliance behavior of TUBERCULOSIS clients in the Puskesmas Juanda area. This study is a descriptive research correlation with the cross-sectional approach. A study was conducted to describe the relationship between independent variables (supervisors of taking drugs by families and health workers) with dependent variables (preventive behavior and compliance of tuberculosis clients) together in a certain period.Keywords: PMO of families and health workers, Preventive Behavior And Compliance of Tuberculosis Sufferers.